IMPROVING STUDENTS’ MATHEMATICAL REASONING IN GEOMETRY USING ADOBE FLASH LEARNING MEDIA - Lutfi, Ahmad Fajri; Yuliardi, Ricki; Nurjanah, Nurjanah (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2018)
The technology era provides new opportunities to improve mathematics teaching and learning. In this paper, we reported the implementation of Adobe Flash as learning media for improving students' reasoning ability. Results suggested a significantly improved reasoning ability in experimental class compared to control class, which indicated the effectiveness of Adobe Flash as media for learning geometry. The use of animation, video, and worked example, foster students’ reasoning ability by making geometrical concepts transparent and reducing possible misleading spatial perception.